Short- and Mid-Term Autograft Outcomes Following the Reinforced Ross Operation. Issue 1 (January 2022) - Leeds, Hayden; Ashfaq, Awais; McGrath, Lidija; Dewey, Elizabeth N.; Ungerleider, Ross M.; Shen, Irving; Muralidaran, Ashok
Background: The Ross operation for aortic valve replacement continues to be a controversial option because of concerns related to late autograft dilation and progressive neo-aortic insufficiency. In 2005, the reinforced Ross procedure was described at our institution to address this problem. We aim to analyze the short and mid-term outcomes following this procedure. Methods: This is a retrospective study of patients who underwent the reinforced Ross operation between 2004 and 2019. A comprehensive chart review was performed. Echocardiograms were independently reviewed by an adult congenital cardiologist. The time to reintervention was evaluated with a Kaplan-Meier curve. Analysis was conducted in JMP 15.1 (SAS Inc., Cary, NC). Results: Twenty-five patients underwent the reinforced Ross operation. Twenty-three patients (92%) had bicuspid aortic valve and the most common indication for surgery was a combination of aortic insufficiency and stenosis (n = 18, 72%). The mean follow-up was 6.1 ± 5.0 years. All patients were alive at the time of follow-up. Six patients (24%), from early in our experience, required subsequent aortic reintervention. Median time to reintervention was 41.8 months (0-81.5 months). Sixteen (64%) patients had less than moderate aortic insufficiency at last follow-up. Additionally, average aortic root measurements remained unchanged. Conclusions: The reinforced Ross technique was initially proposed as a way to mitigate aortic root dilation seen in the traditional Ross procedure. Our experience suggests an associated learning curve with the majority of aortic reinterventions occurring within the first few years following surgery. Continued follow-up is warranted to assess its long-term durability and functionality.